Linear Equations and Systems – Algebra (No Calculator) for the SAT Exam
Preparing for the SAT exam’s Math section requires you to master various algebraic skills, particularly those related to linear equations and systems of linear equations. In the no-calculator portion of the SAT, you need to rely on strong conceptual understanding and efficient problem-solving strategies. This set of 50 practice questions focuses on linear equations and systems of linear equations, giving you step-by-step solutions to each one. By studying these problems, you will improve your ability to manipulate algebraic expressions, solve for unknowns, interpret word problems, and handle simultaneous equations confidently.
In these questions, you will encounter single-variable linear equations, multi-step problems, word problems that model real-world situations, and systems of linear equations with two variables. Each solution is designed to help you see the reasoning process behind the steps, so you can learn not just what to do, but why each step is taken. This approach ensures you build a deeper understanding and can apply the same methods to new problems on the actual SAT.
Because this set of questions is targeted for the no-calculator portion, all arithmetic must be done by hand or with mental math strategies. Wherever possible, we provide tips to simplify the process, such as factoring out common terms or combining like terms carefully. We also touch on strategic guessing when necessary, the importance of verifying each step for accuracy, and how to approach word problems systematically.
In addition to the detailed solutions for each of the 50 practice questions, you will find helpful reminders about crucial algebraic concepts, how to interpret coefficients, constants, and variables, as well as best practices to avoid careless mistakes. By carefully working through these 50 questions, you will hone your skills for the SAT exam and gain confidence in tackling linear equations under time pressure.
Let’s begin! Be sure to take notes, pause after each question, and understand the rationale before moving on. With consistent practice and thorough review, you’ll be well on your way to excelling in the no-calculator section of the SAT Math test.
Question 1
Solve for x in the equation: 3x + 7 = 19.
Solution
To isolate x, we first subtract 7 from both sides of the equation:
3x + 7 = 19
3x + 7 − 7 = 19 − 7
3x = 12
Next, we divide both sides by 3:
x = 12 ÷ 3 = 4
Therefore, x = 4. This problem is a straightforward example of solving a basic linear equation where you aim to isolate the variable by applying inverse operations step by step.
Question 2
Solve for x: 2(x − 4) = 6.
Solution
Distribute the 2 on the left side of the equation:
2(x − 4) = 6
2x − 8 = 6
Now, add 8 to both sides:
2x − 8 + 8 = 6 + 8
2x = 14
Finally, divide both sides by 2:
x = 14 ÷ 2 = 7
Thus, x = 7. Note how distributing a factor across terms inside parentheses is a common first step in many linear equations.
Question 3
If 6x − 3 = 21, what is the value of x?
Solution
Start by isolating the term with x. Add 3 to both sides:
6x − 3 + 3 = 21 + 3
6x = 24
Now divide by 6:
x = 24 ÷ 6 = 4
The answer is x = 4. Checking the work: 6(4) − 3 = 24 − 3 = 21, which confirms the solution is correct.
Question 4
Solve the equation: -5x + 10 = 0.
Solution
Move the constant term to the other side:
-5x + 10 = 0
-5x = -10
Divide both sides by -5:
x = -10 / -5 = 2
Therefore, x = 2. Note that negative divided by negative is a positive value.
Question 5
Solve for x: (1/2)x − 4 = 5.
Solution
First, isolate the term with x by adding 4 to both sides:
(1/2)x − 4 + 4 = 5 + 4
(1/2)x = 9
Multiply both sides by 2 (the reciprocal of 1/2) to solve for x:
x = 9 × 2 = 18
The final answer is x = 18.
Question 6
The equation 4x + 3 = 2x + 17 models a certain relationship. Solve for x.
Solution
To solve for x, first move all x-terms to one side. Subtract 2x from both sides:
4x + 3 − 2x = 2x + 17 − 2x
2x + 3 = 17
Next, subtract 3 from both sides:
2x = 17 − 3
2x = 14
Finally, divide by 2:
x = 14 ÷ 2 = 7
Hence, x = 7.
Question 7
Solve the linear equation: 2(x + 1) - x = 9.
Solution
First, distribute the 2:
2(x + 1) - x = 9
2x + 2 - x = 9
Combine like terms (2x - x):
x + 2 = 9
Subtract 2 from both sides:
x = 7
The result is x = 7.
Question 8
Solve for y: 5 - y = 12.
Solution
Move y to the other side by subtracting 5 or rearrange to isolate y. Let’s isolate y:
5 - y = 12
-y = 12 - 5
-y = 7
Now multiply both sides by -1:
y = -7
Thus, y = -7. Always be careful with negative signs when isolating variables.
Question 9
Solve the equation: 7x - 2 = 5x + 10.
Solution
Subtract 5x from both sides to collect the x terms on one side:
7x - 5x - 2 = 5x - 5x + 10
2x - 2 = 10
Add 2 to both sides:
2x = 12
Divide by 2:
x = 6
Therefore, x = 6.
Question 10
Solve for m in the equation: m/2 + 3 = 1.
Solution
Subtract 3 from both sides to isolate the fraction term:
m/2 = 1 - 3
m/2 = -2
Multiply both sides by 2:
m = -2 × 2 = -4
Hence, m = -4.
Question 11
If 3(2x - 5) = 9, solve for x.
Solution
Distribute 3:
3(2x - 5) = 9
6x - 15 = 9
Add 15 to both sides:
6x = 24
Divide by 6:
x = 4
Thus, x = 4.
Question 12
Solve the equation: 4x + 2 = 3x - 5.
Solution
First, bring the x-terms together by subtracting 3x from both sides:
4x - 3x + 2 = -5
x + 2 = -5
Subtract 2 from both sides:
x = -7
Therefore, x = -7.
Question 13
Solve for x: 8 - 3x = 2x + 13.
Solution
Add 3x to both sides to get all the x-terms on one side:
8 = 5x + 13
Subtract 13 from both sides:
8 - 13 = 5x
-5 = 5x
Divide by 5:
x = -1
Hence, x = -1.
Question 14
Solve the equation for x: 5 - 2x = 4(1 - x).
Solution
Expand the right side:
5 - 2x = 4 - 4x
Add 4x to both sides:
5 + 2x = 4
Subtract 5 from both sides:
2x = -1
Divide both sides by 2:
x = -1/2
Therefore, x = -1/2.
Question 15
Solve for x: (3/4)x = 6.
Solution
Multiply both sides by the reciprocal of (3/4), which is (4/3):
x = 6 × (4/3)
Simplify:
x = (6 × 4) / 3 = 24 / 3 = 8
Hence, x = 8.
Question 16
Solve for x: 9x/3 - 2 = 1.
Solution
First, simplify the term 9x/3:
9x/3 = 3x
So the equation becomes:
3x - 2 = 1
Add 2 to both sides:
3x = 3
Divide by 3:
x = 1
Therefore, x = 1.
Question 17
Solve the following: 10 - 3(2x + 1) = 1.
Solution
Distribute -3:
10 - 3(2x + 1) = 1
10 - 6x - 3 = 1
Combine like terms (10 - 3):
7 - 6x = 1
Subtract 7 from both sides:
-6x = 1 - 7
-6x = -6
Divide by -6:
x = (-6)/(-6) = 1
Hence, x = 1.
Question 18
If (2/3)x + 6 = 10, find x.
Solution
Subtract 6 from both sides:
(2/3)x = 4
Multiply both sides by (3/2), the reciprocal of (2/3):
x = 4 × (3/2) = (4 × 3) / 2 = 12 / 2 = 6
Therefore, x = 6.
Question 19
Solve for x: 12 - x = 2(x + 4).
Solution
Expand the right side:
12 - x = 2x + 8
Add x to both sides to move x terms to the right:
12 = 3x + 8
Subtract 8 from both sides:
4 = 3x
Divide by 3:
x = 4/3
Therefore, x = 4/3 or 1.333... (but since no calculator is needed, 4/3 is a perfectly acceptable answer).
Question 20
Find x if 5(x - 3) = 2x + 10.
Solution
Distribute 5 on the left:
5(x - 3) = 2x + 10
5x - 15 = 2x + 10
Subtract 2x from both sides:
3x - 15 = 10
Add 15 to both sides:
3x = 25
Divide by 3:
x = 25/3
Hence, x = 25/3, which is approximately 8.333....
Question 21
The equation 7 - (x + 2) = 4 holds. Solve for x.
Solution
Distribute the minus sign across (x + 2):
7 - x - 2 = 4
Combine like terms:
5 - x = 4
Subtract 5 from both sides:
-x = -1
Multiply both sides by -1:
x = 1
Thus, x = 1.
Question 22
If 3x + 4 = x + 10, find x.
Solution
Subtract x from both sides:
3x - x + 4 = 10
2x + 4 = 10
Subtract 4:
2x = 6
Divide by 2:
x = 3
Therefore, x = 3.
Question 23
Solve for x: -4x + 9 = 1.
Solution
Subtract 9 from both sides:
-4x = 1 - 9 = -8
Divide both sides by -4:
x = -8 / -4 = 2
Hence, x = 2.
Question 24
Solve: (x/4) + 5 = 7.
Solution
Subtract 5 from both sides:
x/4 = 2
Multiply both sides by 4:
x = 2 × 4 = 8
Therefore, x = 8.
Question 25
Solve the equation: -2x + 3( x - 4 ) = -11.
Solution
Distribute 3:
-2x + 3x - 12 = -11
Combine like terms:
x - 12 = -11
Add 12 to both sides:
x = 1
Hence, x = 1.
Systems of Linear Equations
Now we turn to systems of linear equations. For the no-calculator portion of the SAT, it is crucial to be comfortable solving two-variable systems by elimination, substitution, or by quickly spotting ways to combine equations to solve for variables efficiently.
Question 26
Solve the system:
1) x + y = 5
2) x - y = 1
Solution
One simple method is to add the two equations to eliminate y.
(x + y) + (x - y) = 5 + 1
2x = 6
x = 3
Substitute x = 3 into x + y = 5:
3 + y = 5
y = 2
The solution is (x, y) = (3, 2).
Question 27
Solve the system:
1) 2x + y = 8
2) x - y = 1
Solution
From the second equation, x - y = 1, we can isolate y:
y = x - 1
Substitute y = x - 1 into the first equation 2x + y = 8:
2x + (x - 1) = 8
3x - 1 = 8
Add 1 to both sides:
3x = 9
Divide by 3:
x = 3
Then y = 3 - 1 = 2
So, (x, y) = (3, 2).
Question 28
Solve the system of linear equations:
1) 3x + 2y = 14
2) x - 2y = -10
Solution
From equation 2, x - 2y = -10, we can solve for x:
x = -10 + 2y
Substitute x = -10 + 2y into the first equation:
3(-10 + 2y) + 2y = 14
-30 + 6y + 2y = 14
Combine like terms:
-30 + 8y = 14
Add 30 to both sides:
8y = 44
Divide by 8:
y = 44/8 = 11/2 = 5.5
Now substitute y = 11/2 back into x = -10 + 2y:
x = -10 + 2(11/2) = -10 + 11 = 1
Hence, the solution is (x, y) = (1, 11/2).
Question 29
Solve the system:
1) 2x - y = 4
2) 3x + 2y = 1
Solution
Let’s use elimination. From the first equation, 2x - y = 4, we can solve for y:
-y = 4 - 2x
y = 2x - 4
Substitute y = 2x - 4 into the second equation:
3x + 2(2x - 4) = 1
3x + 4x - 8 = 1
Combine like terms:
7x - 8 = 1
Add 8 to both sides:
7x = 9
Divide by 7:
x = 9/7
Now substitute x = 9/7 into y = 2x - 4:
y = 2(9/7) - 4 = 18/7 - 4
y = 18/7 - 28/7 = -10/7
The solution is (x, y) = (9/7, -10/7).
Question 30
Solve the system using any method:
1) 4x + y = 6
2) 4x - y = 2
Solution
Notice that adding these two equations will eliminate y:
(4x + y) + (4x - y) = 6 + 2
8x = 8
x = 1
Substitute x = 1 back into the first equation, 4(1) + y = 6:
4 + y = 6
y = 2
Thus, the solution is (x, y) = (1, 2).
Question 31
Solve the system:
1) x + 2y = 9
2) 3x + 2y = 15
Solution
Subtract equation 1 from equation 2 to eliminate y:
(3x + 2y) - (x + 2y) = 15 - 9
3x - x + 2y - 2y = 6
2x = 6
x = 3
Substitute x = 3 into x + 2y = 9:
3 + 2y = 9
2y = 6
y = 3
Therefore, (x, y) = (3, 3).
Question 32
Solve the system:
1) 5x - 3y = 0
2) 10x - 6y = 4
Solution
Observe that the second equation 10x - 6y = 4 is essentially twice the first equation 5x - 3y = 0, except for the constant term. Let’s see:
Multiply the first equation by 2:
(5x - 3y) * 2 = 0 * 2
10x - 6y = 0
Compare this to the second equation: 10x - 6y = 4. We have:
10x - 6y = 0 (from doubling eqn. 1)
10x - 6y = 4 (actual eqn. 2)
These two lines are parallel unless 4 = 0, which it does not. Hence, there is no solution. This is an inconsistent system.
Therefore, no solution (the system is inconsistent).
Question 33
Solve the system:
1) y = 2x + 1
2) y = -x + 4
Solution
Since both right sides equal y, set them equal to each other:
2x + 1 = -x + 4
Add x to both sides:
3x + 1 = 4
Subtract 1:
3x = 3
Divide by 3:
x = 1
Substitute x = 1 into y = 2x + 1:
y = 2(1) + 1 = 3
The solution is (x, y) = (1, 3).
Question 34
Solve the system of equations:
1) x = 2y - 5
2) x + y = 7
Solution
From x = 2y - 5, substitute into x + y = 7:
(2y - 5) + y = 7
Combine like terms:
3y - 5 = 7
Add 5 to both sides:
3y = 12
Divide by 3:
y = 4
Substitute y = 4 back into x = 2y - 5:
x = 2(4) - 5 = 8 - 5 = 3
Hence, (x, y) = (3, 4).
Question 35
Solve for x and y:
1) 4x + 2y = 10
2) 2x + y = 5
Solution
Notice that the second equation, 2x + y = 5, can be multiplied by 2 to match the first equation’s coefficients:
Multiply eqn. 2 by 2: 4x + 2y = 10
This is exactly the same as equation 1. Therefore, every solution that satisfies one also satisfies the other. The system represents the same line. Hence, there are infinitely many solutions:
Infinitely many solutions (the equations are dependent).
In slope-intercept form, from 2x + y = 5 => y = 5 - 2x. Any (x, y) pair that satisfies y = 5 - 2x is a solution.
Question 36
Solve the system:
1) 2x + 5y = 1
2) 3x - 5y = 14
Solution
Adding the equations to eliminate y:
(2x + 5y) + (3x - 5y) = 1 + 14
5x = 15
x = 3
Substitute x = 3 into 2x + 5y = 1:
2(3) + 5y = 1
6 + 5y = 1
5y = -5
y = -1
Thus, (x, y) = (3, -1).
Question 37
Solve the system by substitution:
1) x + 3y = 7
2) 2x + y = 4
Solution
From eqn. 1, x + 3y = 7, solve for x:
x = 7 - 3y
Substitute x = 7 - 3y into eqn. 2, 2x + y = 4:
2(7 - 3y) + y = 4
Distribute:
14 - 6y + y = 4
Combine like terms:
14 - 5y = 4
Subtract 14 from both sides:
-5y = -10
Divide by -5:
y = 2
Substitute y = 2 back into x = 7 - 3y:
x = 7 - 3(2) = 7 - 6 = 1
Hence, (x, y) = (1, 2).
Question 38
A system of equations is given as:
1) x - 4y = 5
2) y = x - 1
Solution
Use substitution from eqn. 2, y = x - 1, into eqn. 1:
x - 4(x - 1) = 5
Distribute -4:
x - 4x + 4 = 5
-3x + 4 = 5
Subtract 4 from both sides:
-3x = 1
Divide by -3:
x = -1/3
Now find y:
y = x - 1 = -1/3 - 1 = -1/3 - 3/3 = -4/3
The solution is (x, y) = (-1/3, -4/3).
Question 39
Solve the system:
1) 3x + y = 11
2) 3x - y = 5
Solution
Adding the two equations eliminates y:
(3x + y) + (3x - y) = 11 + 5
6x = 16
x = 16/6 = 8/3
Substitute x = 8/3 into the first equation, 3x + y = 11:
3(8/3) + y = 11
8 + y = 11
y = 3
Hence, (x, y) = (8/3, 3).
Question 40
Solve for x and y:
1) x - 2y = -2
2) 2x + 3y = 11
Solution
From the first equation, x - 2y = -2, solve for x:
x = 2y - 2
Substitute into the second equation 2x + 3y = 11:
2(2y - 2) + 3y = 11
Distribute:
4y - 4 + 3y = 11
Combine like terms:
7y - 4 = 11
Add 4 to both sides:
7y = 15
Divide by 7:
y = 15/7
Then x = 2(15/7) - 2 = 30/7 - 14/7 = 16/7
So, (x, y) = (16/7, 15/7).
Question 41
Solve the system of equations for x and y:
1) y = 2x
2) y + x = 9
Solution
Substitute y = 2x into y + x = 9:
(2x) + x = 9
3x = 9
x = 3
Then y = 2(3) = 6
Hence, (x, y) = (3, 6).
Question 42
Solve for x and y:
1) 4x - y = 3
2) 4x + y = 7
Solution
Add the two equations to eliminate y:
(4x - y) + (4x + y) = 3 + 7
8x = 10
x = 10/8 = 5/4
Substitute x = 5/4 into 4x - y = 3:
4(5/4) - y = 3
5 - y = 3
-y = -2
y = 2
Therefore, (x, y) = (5/4, 2).
Question 43
Solve the system:
1) 3x + 4y = 16
2) x = 2y - 2
Solution
Substitute x = 2y - 2 into 3x + 4y = 16:
3(2y - 2) + 4y = 16
6y - 6 + 4y = 16
10y - 6 = 16
Add 6 to both sides:
10y = 22
y = 22/10 = 11/5
Now substitute y = 11/5 into x = 2y - 2:
x = 2(11/5) - 2 = 22/5 - 10/5 = 12/5
Hence, (x, y) = (12/5, 11/5).
Question 44
Solve the following system:
1) x + 2y = 1
2) 2x + 4y = 2
Solution
Notice the second equation is just 2 times the first. If we multiply x + 2y = 1 by 2, we get 2x + 4y = 2, which is the same as eqn. 2. This means the two equations are dependent, representing the same line.
There are infinitely many solutions. All points (x, y) satisfying x + 2y = 1 are on this line.
Question 45
Solve the system for integers if possible:
1) 3x + 9y = 6
2) x + 3y = 2
Solution
Observe that equation 1 can be simplified by dividing all terms by 3:
3x + 9y = 6 => x + 3y = 2
This is exactly the same as equation 2. So again, we have infinitely many solutions.
Question 46
Solve the system:
1) x + y = 10
2) x + y = 7
Solution
The left sides of the two equations are identical (x + y), but the right sides differ (10 vs. 7). This implies no solution exists because x + y can’t simultaneously be 10 and 7.
Therefore, the system is inconsistent, and there is no solution.
Question 47
Solve the system:
1) 2x - 3y = 1
2) 3x + 2y = 17
Solution
Try elimination. Multiply eqn. 1 by 2, eqn. 2 by 3 to align coefficients:
Eqn. 1 * 2: 4x - 6y = 2
Eqn. 2 * 3: 9x + 6y = 51
Now add these two new equations:
(4x - 6y) + (9x + 6y) = 2 + 51
13x = 53
x = 53/13 = 4.0769... but as a fraction, x = 53/13 = 4 + 1/13
Now substitute x = 53/13 into 2x - 3y = 1:
2(53/13) - 3y = 1
106/13 - 3y = 1
Convert 1 to a fraction with denominator 13: 1 = 13/13
106/13 - 3y = 13/13
Subtract 106/13 from both sides:
-3y = 13/13 - 106/13 = -93/13
Divide by -3:
y = (-93/13) / -3 = 93/13 * 1/3 = 93/39 = 3 * 31 / 3 * 13 = 31/13
So, (x, y) = (53/13, 31/13).
Question 48
Solve for x and y:
1) x - y = 6
2) 2x + y = 9
Solution
Add the two equations to eliminate y:
(x - y) + (2x + y) = 6 + 9
3x = 15
x = 5
Substitute x = 5 into x - y = 6:
5 - y = 6
-y = 1
y = -1
Hence, (x, y) = (5, -1).
Question 49
Solve the system:
1) 2x - y = 3
2) 3x + y = 7
Solution
Add the equations to eliminate y:
(2x - y) + (3x + y) = 3 + 7
5x = 10
x = 2
Substitute x = 2 into 2x - y = 3:
2(2) - y = 3
4 - y = 3
-y = -1
y = 1
The solution is (x, y) = (2, 1).
Question 50
Solve for x and y:
1) y = -3x + 12
2) y = x - 8
Solution
Since both expressions equal y, set them equal:
-3x + 12 = x - 8
Add 3x to both sides:
12 = 4x - 8
Add 8 to both sides:
20 = 4x
x = 20/4 = 5
Substitute x = 5 back into y = x - 8:
y = 5 - 8 = -3
Hence, (x, y) = (5, -3).
Conclusion and Final Tips
Congratulations on working through these 50 practice questions focused on linear equations and systems of linear equations for the no-calculator portion of the SAT exam. Here are a few final tips to help you strengthen your algebra skills and maximize your performance on test day:
- Practice Mental Math: Since you cannot use a calculator for these problems, build up your mental arithmetic skills. This includes adding and subtracting integers quickly, multiplying and dividing small fractions, and reducing fractions to simplest form.
- Check for Mistakes: Simple sign errors or overlooked common factors can turn an easy problem into a nightmare. Always verify your steps, especially when manipulating negative terms and fractions.
- Master Elimination and Substitution: In the SAT, either method can be efficient, but sometimes one approach is simpler than the other. Learn to recognize which method is faster given a particular problem structure.
- Watch Out for Special Cases: Systems with no solution or infinitely many solutions appear in the SAT. Recognize parallel lines and overlapping lines quickly by comparing coefficients.
- Translate Word Problems Carefully: While these 50 questions were primarily symbolic, be prepared for real-world scenarios on the SAT. Convert each sentence into an equation step by step.
By mastering these core algebraic manipulations, you build a solid foundation not only for the SAT but also for more advanced math courses. Keep practicing, and best of luck on your upcoming exam!